The Influence of Digital Marketing and Market Orientation on Sales Performance Through Product Innovation and Product Excellence - Amin, Mokhamad; Suliyanto; Tabrani (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
Micro, Small and Medium Enterprises (MSMEs) in running their business need a strategy to achieve the desired goals. MSMEs must maximize sales performance including through Digital Marketing, Orientation, Product Innovation and Product Excellence. The purpose of this study is to analyze the effect of market orientation on product innovation, analyze the effect of market orientation on product excellence, analyze the effect of product innovation on product excellence, analyze the effect of digital marketing on sales performance. analyze the effect of excellence on sales performance. The population in this study are MSMEs in Brebes Regency. The sample used in this study was 95 SMEs in Tegal Regency. The technique used in sampling is purposive sampling, namely sampling with certain considerations or criteria. The data used in this research is primary data, which is done by survey method through questionnaires. The analysis method used is SEM PLS. Based on the results of the study, that the variables Digital Marketing, Market Orientation, Product Innovation, Product Excellence Have a Significant Positive Influence on Sales Performance.